ED-05 GENDER AND REPRODUCTIVE FACTORS IN RELATION TO SURVIVAL IN GLIOBLASTOMA - Egan, Kathleen (Oxford University Press, 2014)
BACKGROUND: Glioblastoma multiforme (GBM) is the most common and lethal primary tumor of the brain. Known clinical prognostic factors include patient age, surgical extent of tumor resection (EOR), and functional performance (Karnofsky) status (KPS). A few studies have suggested differential survival by gender though to our knowledge no study has examined the prognostic impact of reproductive history and hormonal exposures in women. We evaluated gender-specific mortality in a large cohort of GBM patients that underwent current standard of care and investigated clinical, tumor, and reproductive factors associated with gender-specific differences in survival. METHODS: Analyses were based on 550 patients with GBM (324 men and 226 women) diagnosed 2007-2012 and enrolled in a clinic-based case-control study conducted at medical centers in the Southeast. Information on reproductive and hormonal exposures in women was available from the study interview. RESULTS: Deaths from GBM were documented in 449 patients a median of 17.2 months following diagnosis (16.0 months in men and 18.6 months in women). Men and women were similar in age at diagnosis (median of 59 and 60 years, respectively; P= 0.992), education (41% and 39%, respectively, held a college degree; P= 0.749), KPS (median of 90% in both groups; P = 0.167), and EOR (32% and 29%, respectively, with gross total resection; P= 0.547). A college degree or higher education was independently associated with prolonged survival (multivariate-adjusted p = 0.003). Adjusting for age, education, EOR and KPS, the hazard of death was significantly greater in men (Hazard Ratio (HR): 1.25; 95% Confidence Interval (CI): 1.03, 1.51; p = 0.026). When compared to men, a reduced hazard was observed among parous women (HR: 0.78; p = 0.022) and in those that ever used hormonal replacement therapy (HR: 0.67; p = 0.016) controlling for other covariates. CONCLUSIONS: Reproductive history and exogenous hormones may contribute to a female survival advantage in patients with GBM.